Measuring Parcel Service Quality in University using Servqual Model - Muhammad Ashlyzan Razik; Norlinda Mohd Rozar; Mohd Nor Hakimin Yusoff; Hasannuddiin Hassan; Ainon @ Jamilah Binti Ramli; Rosmaizura Binti Mohd Zain (International Journal of Supply Chain Management, 2018)
Service quality (SERVQUAL MODEL) is among the most crucial determinant for customer satisfaction in the parcel service industry. It consists of tangibility, reliability, assurance, empathy and responsiveness. This model greatly affects customer satisfaction. The purpose of the research is to examine the effects of the factors of SERVQUAL MODEL towards customer satisfaction in University Malaysia Kelantan (UMK) City Campus students in the case of HEP Parcel Service Quality. A structured questionnaire was developed to be answered by 246 students in UMK City Campus. All factors of SERVQUAL toward the HEP parcel service have the association with the satisfaction of UMK students and it has proven in the results. Research have recommend University Malaysia Kelantan (UMK) to further improve their HEP Parcel Service Quality and pay higher attention towards it to increase student usage and satisfaction.